Assess Knowledge, Attitude, and Practice Towards Food Safety and Hygiene of Students of Faculty of Environmental Sciences, VNU University of Science - Thi Minh Hang, Tran; Thi Huong Thao, Trinh; Ha Vy, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
Food Safety and Hygiene (FSH) affect not only human health but also economic and social development. In Vietnam, food safety remains an issue specially in environment where students are independent in their eating habits yet still lack of the FSH skills. Understanding the status of students’ awareness in applying FSH principles is crucial. This study assessed the knowledge, attitudes, and practices (KAP) of 286 students from the Faculty of Environmental Sciences, VNU University of Science, through a cross-sectional survey using a standardized questionnaire. The findings showed that 74.8% of students had substantial FSH knowledge, 76.2% expressed positive attitudes toward FSHs showed that genders, field of studies, and place of residences showed a significant effect on KAP scores. Female students and those in food-related majors generally had higher KAP score. The study proposed some measures to improve FSH awareness among student community such as enhancing digital communication, offering hands-on training sessions, promoting awareness of FSH laws within universities, and developing educational programs relating to FSH and sustainable consumption.